Translating Mechanism of Regulatory Action of Tolerogenic Dendritic Cells to Monitoring Endpoints in Clinical Trials - Suwandi, Jessica S.; Nikolic, Tatjana; Roep, Bart O. (Frontiers in Immunology, 2017)
Tolerogenic dendritic cells (tolDCs) have reached patients with autoimmune and inflammatory disease, at least in clinical trials. The safety of tolDCs as intervention therapy has been established, but the capacity to modulate autoimmune response in vivo remains to be demonstrated. Studies have revealed a diversity of regulatory mechanisms that tolDCs may employ in vivo. These mechanisms differ between various types of modulated tolDC. The most often foreseen action of tolDCs is through regulatory polarization of naïve T cells or activation of existing regulatory T cells (Tregs), which should ultimately diminish autoimmune inflammation. Yet, selection of a target auto-antigen remains critical to expedite tissue specific tolerance induction, while measuring immune modulation incited by tolDCs in vivo provides a great challenge. We will discuss the regulatory action of different types of tolDCs and the possible methods to monitor immunological efficacy endpoints for the next generation clinical trials.